2015
DOI: 10.1682/jrrd.2014.06.0154
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous pain inhibition is unrelated to autonomic responses in acute whiplash-associated disorders

Abstract: Abstract-Patients with acute whiplash-associated disorder (WAD) demonstrate an inefficient endogenous pain inhibition and may experience a dysfunction in autonomic nervous system reactivity to pain. This study compared the autonomic response to painful stimuli between patients with acute and chronic WAD and healthy controls. In addition, the role of the autonomic nervous system for explaining inefficient endogenous pain inhibition was examined in acute WAD. Seventeen patients with acute WAD, 30 patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
(48 reference statements)
1
14
0
2
Order By: Relevance
“…study that also did not observe differences between the parasympathetic cardiac modulation at rest in patients with acute and chronic pain after a whiplash injury (30). Painful stimuli and many pain conditions are related to enhancing of sympathetic activity (30,(33)(34)(35)(36). Indeed, the use of beta-blockade decreased pain intensity (33) and noradrenaline injection increased it (37).…”
Section: Characteristicsmentioning
confidence: 82%
See 1 more Smart Citation
“…study that also did not observe differences between the parasympathetic cardiac modulation at rest in patients with acute and chronic pain after a whiplash injury (30). Painful stimuli and many pain conditions are related to enhancing of sympathetic activity (30,(33)(34)(35)(36). Indeed, the use of beta-blockade decreased pain intensity (33) and noradrenaline injection increased it (37).…”
Section: Characteristicsmentioning
confidence: 82%
“…The deterioration of the cardiac parasympathetic regulation of the patients with impaired DNIS may be related to the central nervous system function modifica-tions. In patients with a whiplash injury, no association was observed between the parasympathetic branch and the CPM, although it was observed that patients with chronic injury showed correlations between HRV variables and the impairment of the endogenous analgesia (30). Data from neuroimaging studies demonstrate that chronic pain is associated with anatomical and functional modifications in different brain areas (31).…”
Section: Discussionmentioning
confidence: 97%
“…One normally finds that pain to the test stimulus is less when applied along with another pain stimulus than when presented alone. The reduced efficacy of CPM has been found in several patient populations including fibromyalgia, irritable bowel syndrome (IBS), temporomandibular disorder (TMD), and whiplash-associated disorders (Wijk & Veldhuijzen, 2010;De Kooning et al, 2015;Kennedy et al, 2016).…”
Section: Assessment Of Sensitizationmentioning
confidence: 99%
“…There is some evidence that ANS balance influences the endogenous inhibitory pain network in individuals with chronic pain conditions . One non‐invasive approach to assessing ANS activity is heart rate variability (HRV).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that ANS balance influences the endogenous inhibitory pain network in individuals with chronic pain conditions. [15][16][17] One non-invasive approach to assessing ANS activity is heart rate variability (HRV). Heart rate variability is a measure of the heart period variability based on within-subject statistical or time-series summarization of sequences of measured normal RR intervals.…”
Section: Introductionmentioning
confidence: 99%